2013
DOI: 10.1073/pnas.1301464110
|View full text |Cite
|
Sign up to set email alerts
|

Nematic liquid crystal boojums with handles on colloidal handlebodies

Abstract: Topological defects that form on surfaces of ordered media, dubbed boojums, are ubiquitous in superfluids, liquid crystals (LCs), Langmuir monolayers, and Bose-Einstein condensates. They determine supercurrents in superfluids, impinge on electrooptical switching in polymerdispersed LCs, and mediate chemical response at nematic-isotropic fluid interfaces, but the role of surface topology in the appearance, stability, and core structure of these defects remains poorly understood. Here, we demonstrate robust gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(116 citation statements)
references
References 39 publications
5
111
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Two- [7][8][9][10][11] and three-dimensional 14 crystals were designed in nematics using different elastic dipoles and quadrupoles, and singular defects were tailored using spherical 16 and topologically non-trivial 17 colloidal particles. Recent studies also showed the importance of size [18][19][20][21][22][23][24] and shape [24][25][26][27][28][29][30][31] in elastic interactions and ensuing assemblies of colloidal particles in nematics. On the other hand, colloidal dispersions in twisted nematic and cholesteric LCs (CLCs) have received less attention [32][33][34][35][36][37][38][39][40][41][42][43]<...>…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Two- [7][8][9][10][11] and three-dimensional 14 crystals were designed in nematics using different elastic dipoles and quadrupoles, and singular defects were tailored using spherical 16 and topologically non-trivial 17 colloidal particles. Recent studies also showed the importance of size [18][19][20][21][22][23][24] and shape [24][25][26][27][28][29][30][31] in elastic interactions and ensuing assemblies of colloidal particles in nematics. On the other hand, colloidal dispersions in twisted nematic and cholesteric LCs (CLCs) have received less attention [32][33][34][35][36][37][38][39][40][41][42][43]<...>…”
Section: Introductionmentioning
confidence: 99%
“…The total winding number of boojums in the projection of n(r) to the particle surface, n s (r), is always  i s i =, also satisfying topological theorems (92). These simple relations describe defects induced both by the g=0 spherical surfaces (Figures 1 and 2) and by surfaces like handlebodies and torus knots with g0 (Figure 6), though additional self-compensating defects can appear to reduce the energetic cost of elastic distortions associated with matching BCs on colloidal surfaces to n 0 .…”
mentioning
confidence: 99%
“…However, beyond the predictions of topological theorems, it was found that nematic colloids can also have mutually tangled physical knots of particles and line defects in n(r), as illustrated in Figure 6j-l (93). For all nematic colloidal particles, the interplay of topologies of surfaces, fields, and defects guides n(r) to comply with the particle shape, generating knotted, linked, and other 3D configurations (91)(92)(93)(94), providing experimental insights into the aspects of the mathematical knot theory (90,93,94).…”
mentioning
confidence: 99%
“…Among these materials, colloidal dispersions of microparticles and nanoparticles in LCs have been actively studied in research on soft-matter physics (2)(3)(4)(5)(6)(7). Tunable anisotropic interactions between microparticles dispersed in LCs give rise to self-assembled 1D and 2D colloidal structures (6,8,9). Such colloidal dispersions are interesting not only from a fundamental point of view but also from a technological one.…”
mentioning
confidence: 99%